Evaluasi Geometri Peledakkan Berdasarkan Pengaruh Perhitungan Blastability Index Untuk Mendapatkan Fragmentasi Ideal Pada Front Penambangan Di PT. Ansar Terang Crushindo 1 Pangkalan Koto Baru Kabupaten Lima Puluh Kota Sumatera Barat. - Naufal Permanda; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Geometric Determination of blasting and powder factor must show the rock mass characteristics and local geological conditions. Alternative geometry experiments were carried out to solve the resulting blasting problem. The alternative geometry design is determined using rock mass characteristics based on the Lilly Blastability Index, in the form of rock mass description, joint plane spacing, joint plane orientation, specific gravity influence and hardness. Based on the weighted results of the blasted rock mass, the Blastability Index value is 58.075. From the value, good blasting geometries are 3 inch boreholes, 2 m burden, 3 m spacing, 3.2 m blast hole, 0.2 m subdrilling, 3 m level height, 2.17 m steaming and material filling and 1.03 m explosive, 0.22 kg / m3 powder factor. From the results of the proposed geometry based on the lilly equation, the percentage of boulder desired by the company and the use of explosives is lower than the previously applied geometry.Keywords: rock mass characteristics, blastability index, geometry, balasting, fragmentation